Love Addiction among Soran University Students - Hewa Abdulazeez Jameel; Daryoush Mueen Qader (Zanco Journal of Human Sciences, 2025)
Love addiction dates back to the 1970s, which refer to Inappropriate, widespread, and excessive desire for one or more romantic partners that leads to inability to control behavior and give up the individual's specific passions and desire. The current research aims to determine the level of love addiction among students at Soran University, and the difference between them by the demographic variable of (Gender, age, and economic status). Quantitative descriptive method was used to analyze the data. The sample comprised (244) students, (120) males, and (124) females, aged from (18 to 25). The results indicated a low level of love addiction among participants. In term of demographic variables significant differences were recorded. Females had higher levels of love addiction, and those who are in older ages and better economic status had higher levels of love addiction. Hence, based on the study findings a number of recommendations can be devoted for further research.